2022
DOI: 10.3390/healthcare10071308
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Delivery Is Associated with Postpartum Depression: Do Women with and without Depression History Exhibit a Difference?

Abstract: Whether the mode of birth delivery correlates with the incidence of postpartum depression (PPD) is still under debate. This study seeks to clarify such a correlation and to further investigate if there are any differences in the likelihood of PPD medical care use among women with and without a history of depression. A logistic regression at two assessment points (6-month and 12-month postpartum) on the National Health Insurance Database in Taiwan is performed. In total, 32,729 women were included who gave firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…The analysis of both CS and PPD in each of the seven largest studies ( 21 23 , 25 , 31 , 33 , 34 ) revealed that they accounted for more than 99% of the total cases in this meta-analysis, with a sample size exceeding 10,000. A weaker correlation (OR=1.19, 95% CI: 1.11-1.27, I 2 = 24%, P<0.001) was observed between CS and PPD for the group with over 10,000 participants, compared to the group with fewer than 10,000 participants (OR=1.44, 95% CI: 1.26-1.64, I 2 = 0%, P<0.001) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…The analysis of both CS and PPD in each of the seven largest studies ( 21 23 , 25 , 31 , 33 , 34 ) revealed that they accounted for more than 99% of the total cases in this meta-analysis, with a sample size exceeding 10,000. A weaker correlation (OR=1.19, 95% CI: 1.11-1.27, I 2 = 24%, P<0.001) was observed between CS and PPD for the group with over 10,000 participants, compared to the group with fewer than 10,000 participants (OR=1.44, 95% CI: 1.26-1.64, I 2 = 0%, P<0.001) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 80%
“…There were 14 cohort studies and 4 case-control studies, with the sample size ranging from 60 to 511,422 participants. Specifically, eleven studies ( 11 , 24 , 26 30 , 32 , 35 37 ) had <10,000 participants, while the remaining seven studies ( 21 23 , 25 , 31 , 33 , 34 ) had >10,000 participants. Furthermore, ten studies ( 21 , 23 , 26 , 28 31 , 34 , 36 , 37 ) were conducted in Asia, whereas seven studies ( 22 , 24 , 25 , 27 , 32 , 33 , 35 ) were carried out in Europe, one studies ( 11 ) were conducted in North America.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in a study conducted in Japan on 89,954 women, those who underwent CS delivery were considered a target for PPD monitoring [ 17 ]; the same conclusion was also suggested by Heba Kamal Meky in their cross-sectional study [ 15 ]. A previous study conducted in Taiwan reported that CS was linked to an increased risk of PPD regardless of whether the women had a history of depression [ 18 ].…”
Section: Discussionmentioning
confidence: 99%